2019
DOI: 10.15386/mpr-1213
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and radiographical comparison of buccolingual crestal bone changes after immediate and delayed implant placement

Abstract: AimThe study aims to clinically and radiographically compare the bucco-lingual crestal bone changes after immediate and delayed placement of implants.MethodsTwo groups that consisted of fifty implants were considered for this study. In group A the implants were placed immediately post extraction, whereas, in group B implants placement were delayed by four to six weeks. All the implants were submerged within the alveoli confines. Bone grafts were only placed if the jumping distance was more than 1.5 mm. Barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Other research indicated that the delayed group appeared to have more bone volume loss than the contemporaneous group surrounding a single-crown supported by dental implants [28]. Late placements are also not recommended, according to Schroop and Wenzel et al, they are associated with a buccolingual ridge reduction of approximately 50% of the initial ridge width over a 1-year period, with 2/3 of this bone remodelling arising during the first three months of recovery [11]. Additionally, Bilhan et al illustrated that when implant placement was delayed due to disuse atrophy, bone loss was greater [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research indicated that the delayed group appeared to have more bone volume loss than the contemporaneous group surrounding a single-crown supported by dental implants [28]. Late placements are also not recommended, according to Schroop and Wenzel et al, they are associated with a buccolingual ridge reduction of approximately 50% of the initial ridge width over a 1-year period, with 2/3 of this bone remodelling arising during the first three months of recovery [11]. Additionally, Bilhan et al illustrated that when implant placement was delayed due to disuse atrophy, bone loss was greater [29].…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of immediate implants into extraction sockets versus delayed implants, there is no necessity to wait for the bone to get thicken for 4-6 months after extraction [9], and measurement of Crestal bone loss is lower in immediately inserted implants than those in delayed inserted implants [10]. When compared delayed to immediately inserted implants, they have a lower tissue dehiscence in membrane-based regeneration, and improve bone repair is obtained due to undamaged clotting and possibly due to entire closure of a flap [11]. However, this approach is frequently associated with residual gaps between the residual bone walls and the coronal part of the implant; there is an increased risk of infection and failure if the socket gets contaminated [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted in systematic reviews that, to reduce risks, "immediate implant" insertion should ideally be carried out in a meticulously chosen group of patients. Orofacial soft tissue flattening and facial mucosal recession could be drawbacks for immediate insertion in less favourable instances [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they cautioned that complete preservation of the pre-extraction ridge dimensions in all sites should not be anticipated, as a small amount of crestal dimensional change can still occur after SA. Histological analysis found both biomaterials to have supported new bone regeneration by the process of osteoconduction at the apical and the middle part of the socket [ 72 ].…”
Section: Indications For Socket Augmentationmentioning
confidence: 99%